Soybean rust-resistant and tolerant varieties identified through the Pan-African Trial Network - Favoretto, V.R.; Murithi, H.; Leles, E.P.; da Santos, F.M.; Chigeza, G.; Goldsmith, P.; Coyne, D.; Clough, S.J. (2025)
BACKGROUND The global demand for soybeans is increasing rapidly, with projections indicating an escalation of 70–80 million metric tons over the next decade. Sub-Saharan Africa (SSA) contributes significantly to this growth, with soybean production increasing by 6.8% per year, outpacing the global average increase of 4.7%. Despite the expansion, soybean productivity in Africa remains less than half of the global average. This yield gap is largely due to diseases and pests, such as soybean rust, which can be particularly severe. Effective management of soybean rust depends on several factors, including resistant cultivars. However, there has been limited information on the rust-resistance levels of African cultivars. To address this gap, the Pan-African Trial network conducted soybean varietal trials across diverse locations.